Do clinical incidents, complaints and medicolegal claims overlap?. Issue 8 (12th October 2015) - Goldsmith, Paul; Moon, Jackie; Anderson, Paul; Kirkup, Steve; Williams, Susan; Gray, Margaret
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Error reporting by healthcare staff, patient-derived complaints and patient-derived medico-legal claims are three separate processes present in most healthcare systems. It is generally assumed that all relate to the same cases. Given the high costs associated with these processes and strong desire to maximise quality and standards, the purpose of this paper is to see whether it was indeed the case that most complaints and claims related to medical errors and the relative resource allocation to each group. Design/methodology/approach – Electronic databases for clinical error recording, patient complaints and medico-legal claims in a large NHS healthcare provider organisation were reviewed and case overlap analysed. Findings – Most complaints and medico-legal claims do not associate with a prior clinical error. Disproportionate resource is required for a small number of complaints and the medico-legal claims process. Most complaints and claims are not upheld. Research limitations/implications – The authors have only looked at data from one healthcare provider and for one period. It would be useful to analyse other healthcare organisations over a longer time period. The authors were unable to access data on secondary staffing costs, which would have been informative. As the medico-legal process can go on for many years, the authors do not know the ultimate outcomes for all cases. The authors also do not know how many medico-legal cases were settled out of court pragmatically to minimise costs. Practical implications – Staff error reporting systems and patient advisory services seem to be efficient and working well. However, the broader complaints and claims process is costing considerable time and money, yet may not be useful in driving up standards. System changes to maximise helpful complaints and claims, from a quality and standards perspective, and minimise unhelpful ones are recommended. Originality/value – This study provides important data on the lack of overlap between errors, complaints and claims cases.